A modified alternating direction method for convex quadratically constrained quadratic semidefinite programs - Sun, Jie; Zhang, S. (Elsevier BV * North-Holland, 2010)
We propose a modified alternating direction method for solving convex quadratically constrained quadratic semidefinite optimization problems. The method is a first-order method, therefore requires much less computational effort per iteration than the second-order approaches such as the interior point methods or the smoothing Newton methods. In fact, only a single inexact metric projection onto the positive semidefinite cone is required at each iteration. We prove global convergence and provide numerical evidence to show the effectiveness of this method.